Pengaruh Kepemimpinan dan Total Quality Management terhadap Kualitas Layanan Pendidikan: Studi Komparatif Perspektif Siswa dan Guru - Desi Kardini Wulansari; Dinda Nurul Inayati; Suhendra (Kelola: Jurnal Manajemen Pendidikan, 2025)
This study examines the influence of leadership and the implementation of Total Quality Management (TQM) on the quality of educational services from the perspectives of teachers and students. Ensuring service quality is essential for schools to remain competitive amid globalization and rapid technological change. Using a quantitative approach with a cross-sectional correlational design, data were collected from 100 respondents (75 students and 25 teachers) through Likert-scale questionnaires. Data analysis employed correlation tests, simple and multiple regression, along with classical assumption tests. The results indicate that leadership and TQM simultaneously have a significant effect on the quality of educational services, with R² values of 0.809 (teachers) and 0.669 (students). However, partial analysis shows that only TQM exerts a statistically significant influence, while the effect of leadership becomes insignificant when controlled alongside TQM. These findings highlight that TQM principles—such as continuous improvement, broad participation, and a focus on customer satisfaction—are the dominant determinants of service quality. The novelty of this study lies in demonstrating the comparative weight of TQM and leadership within the Indonesian school context, showing that effective leadership alone is insufficient without a systematic quality management framework. The study contributes to the theory of educational leadership by clarifying its enabling role in implementing TQM, and to TQM theory by emphasizing its central role in educational service delivery. Practically, the findings suggest that schools and policymakers should prioritize comprehensive TQM adoption supported by transformational leadership to sustain quality improvements.